ChemInform Abstract: Regiospecific Synthesis of 2‐Halo‐3‐(2′‐glucalyl)benzo[b]thiophenes. Issue 7 (29th January 2015) - Kinfe, Henok H.; Makolo, Felix L.; Adokoh, Christian K.
Abstract Aryl‐S‐glucosides react with chloroform or bromoform via a carbene insertion and a sigmatropic rearrangement to give novel 2‐halo‐3‐glucalyl substituted benzo[b]thiophenes.